Polyamorphic amorphous silicon at high pressure: raman and spatially resolved X-ray scattering and molecular dynamics studies. - Daisenberger, D; Deschamps, T; Champagnon, B; Mezouar, M; Quesada Cabrera, R; Wilson, M; McMillan, P (2011)
We studied the low-frequency Raman and X-ray scattering behavior of amorphous silicon (a-Si) at high pressure throughout the range where the density-driven polyamorphic transformation between the low-density amorphous (LDA) semiconductor and a novel metallic high-density amorphous (HDA) polyamorph occurs. The experimental data were analyzed with the aid of molecular dynamics (MD) simulations using the Stillinger-Weber potential. The heat capacity of a-Si obtained from the low pressure Raman data exhibits non Debye-like behavior, but the effect is small, and our data support the conclusion that no boson peak is present. The high-pressure Raman data show the presence of a distinct low frequency band for the HDA polyamorph in agreement with ab initio MD simulations. Spatially resolved synchrotron X-ray diffraction was used to study the high pressure behavior of the a-Si sample throughout the LDA-HDA transition range without interference by crystallization events. The X-ray data were analyzed using an iterative refinement strategy to extract real-space structural information. The appearance of the first diffraction peak (FDP) in the scattering function S(Q) is discussed in terms of the void structure determined from Voronoi analysis of the MD simulation data.